Comparative Study on Corrosion Behavior of SA213T22 and SA213T91 Steels in Molten Salt Environment of Na2SO4-60% V2O5 at 900oC - Mittal, Rutash; Goyal, Lucky; Sidhu, Buta Singh (Asian Review of Mechanical Engineering, 2013)
The hot corrosion behavior of boiler tube steels SA213T91 (T91) and SA213T22 (T22) after exposure to molten salt of Na2SO4 – 60% V2O5 were investigated at a temperature of 900oC in a cyclic manner. Thermo-gravimetric technique was used to establish oxidation kinetics for T91 and T22 steels in salt at 900oC under cyclic conditions for 50 cycles. X-ray diffraction (XRD) and scanning electron microscopy/ Energy dispersive spectrometry (SEM/EDS) techniques were used to characterize the oxide scales. The hot corrosion behavior of T91 steel was found to be better than T22 steel exposed to oxidation under salt condition.